TanDEM-X DEM Performance and Calibration - Bachmann, Markus; Bräutigam, Benjamin; Gonzalez, Jaime Hueso; Krieger, Gerhard; Martone, Michele; Rizzoli, Paola; Schulze, Daniel; Schwerdt, Marco; Antony, John Walter; Zink, Manfred (CEOS SAR Workshop on Calibration and Validation (CEOS SAR CalVal), 2011)
The paper describes the actual status of the TanDEM-X DEM Performance and Calibration
DLR Import::2019-04-03